Field Experiments and Behavioral Theories: Science and Ethics. Issue 1 (January 2020) - Carlson, Elizabeth
ABSTRACT: The design of field experiments makes them inappropriate for testing many common political theories. These theories propose that certain factors—for example, income or information—affect how individuals make choices. To test these theories, researchers typically investigate the correlation between the relevant factor and individuals' choices, holding other factors constant. Field experiments, in contrast, allow multiple factors to vary at once: they create real-world disruption and do not control how actors behave in response. Subjects' choices will be affected by the experimental treatment as well as by other changes that occur as the larger system reacts. It will be difficult to isolate the effect of any one factor, particularly without a good preexisting model of the system and how it is likely to respond. If a field experiment will not tell us what we need to know, the benefit of the study cannot outweigh harm, and it also will be unethical.